Long-term Efficacy and Safety of Erenumab: Results From 64 Weeks of the LIBERTY Study. (1st June 2021) - Goadsby, Peter J.; Reuter, Uwe; Lanteri-Minet, Michel; Paiva da Silva Lima, Gabriel; Hours-Zesiger, Peggy; Fernandes, Chrystel; Wen, Shihua; Tenenbaum, Nadia; Kataria, Aditi; Ferrari, Michel D.; Klatt, Jan
Abstract : Objective: To report the efficacy and safety of erenumab among patients with episodic migraine (EM) who were unsuccessful on 2 to 4 preventive treatments observed at week 64 of the open-label extension phase (OLEP) of A Study Evaluating the Effectiveness of AMG 334 Injection in Preventing Migraines in Adults Having Failed Other Therapies (LIBERTY) study (ClinicalTrials.gov NCT03096834). Methods: The OLEP, evaluating monthly erenumab 140 mg for 3 years, enrolled 240 patients who completed the double-blind treatment phase (DBTP) of 12 weeks during which they received placebo or erenumab 140 mg subcutaneous injections every 4 weeks as monotherapy. Efficacy outcomes were evaluated through the initial 52 weeks of OLEP (from DBTP baseline to total 64 weeks) in the overall population, patients receiving erenumab in DBTP, and patients from the DBTP placebo arm who switched to erenumab in OLEP. Endpoints included reduction of ≥50% in monthly migraine days (MMD) from DBTP baseline and change in MMD from DBTP baseline, Headache Impact Test score, and Migraine Physical Function Impact Diary score (Physical Impairment and Everyday Activities). Results: Altogether, the week 52 visit of the OLEP was completed by 204 of 240 (85.0%) patients. Among patients continuing erenumab, the 50% responder rate increased from 29.9% at weeks 9 to 12 to 44.3% at weeks 61 to 64. The 50% responder rate in patients who initiated erenumab in the OLEP remained higher in the OLEP (50.0% at week 61–64) than during DBTP (14.2% at weeks 9–12) compared to patients in continuous erenumab arm. In the OLEP, the 50% responder rate for the overall population increased from weeks 13 to 16 until weeks 37 to 40 and then remained stable through weeks 61 to 64. Patients treated with erenumab in DBTP showed sustained effects on all efficacy outcomes; those initiating erenumab in the OLEP demonstrated continued improvement from week 13 onward. Adverse events (AEs) were reported, considering both treatment groups, by ≈80.8% (serious AEs by 6.7%), 76.3% (5.9%) in the continuing erenumab arm, and 85.2% (7.4%) in those starting erenumab in OLEP. No deaths were reported. Conclusions: In patients with EM who were unsuccessful on 2 to 4 prior preventive treatments, the LIBERTY study demonstrated sustained efficacy on erenumab monotherapy treatment through 64 weeks in both treatment arms. Safety of erenumab was consistent with that observed in previous clinical trials. Trial Registration Information: ClinicalTrials.gov Identifier : NCT03096834. Classification of Evidence: The current study provides Class IV evidence on data from patients with EM that erenumab is safe and provides sustained efficacy at 52 weeks.